Адмністративна процедура та її співвідношення із суміжними поняттями - Гаріфуллін, М. В.; Harifullin, M. V. (Науковий вісник Дніпровського державного університету внутрішніх справ. - 2024. - № 1. - С. 381-388, 2024)
Розглянуто принципове значення понять «адміністративний процес», «адміністративна процедура» та «адміністративне провадження», а також складні зв’язки між ними у сфері правової доктрини. Правильне розуміння та застосування цих термінів має першочергове значення для забезпечення ефективного правового регулювання та захисту прав, свобод і законних інтересів фізичних та юридичних осіб у їхніх відносинах із органами державного управління та судовою системою. Акцентовано на тому, що використання специфічних термінів у законодавчих актах і правових документах відіграє ключову роль у формуванні практики адміністративного права. Незважаючи на різницю в термінології в різних країнах із розвиненими системами адміністративного права, головна мета залишається незмінною – досягти чесного та справедливого адміністративного процесу, котрий підтримує права та інтереси всіх зацікавлених сторін. Проаналізовано відмінності між адміністративним процесом, адміністративною процедурою та адміністративним провадженням шляхом висвітлення їх окремого застосування та наслідків у юридичній практиці.

The basic meaning of the concepts «administrative process», «administrative procedure» and «administrative proceeding» is considered, as well as the complex relationships between them in the field of legal doctrine. The correct understanding and application of these terms is of primary importance for ensuring effective legal regulation and protection of the rights, freedoms and legitimate interests of individuals and legal entities in their relations with public administration bodies and the judicial system. Emphasis is placed on the fact that the use of specific terms in legislative acts and legal documents plays a key role in shaping the practice of administrative law. Despite the difference in terminology in different countries with developed systems of administrative law, the main goal remains the same – to achieve a fair and just administrative process that supports the rights and interests of all interested parties. The differences between the administrative process, administrative procedure and administrative proceedings are analyzed by highlighting their separate application and consequences in legal practice. In addition, the importance of effective legal regulation and its impact on the quality of administrative practice was investigated. It is argued that the use of appropriate terms not only helps in the development of well-defined legal processes, but also contributes to the consistent interpretation and application of laws by public administration and courts. Consequently, this synergy leads to the protection and strengthening of human rights and promotes the legal activity of legal entities. Administrative procedures in various countries with developed systems of administrative law have been studied in detail in order to make comparisons and obtain important conclusions. The study emphasizes that although terminological variations may exist, the ultimate goal is universal – the fair realization and protection of individual and collective rights and interests within administrative interaction. The urgent need for a harmonized approach to administrative procedure and terminology in different jurisdictions is emphasized. Such standardization will not only improve legal clarity, but also strengthen international cooperation and cross-border legal practice.

Рассмотрено принципиальное значение понятий «административный процесс», «административная процедура» и «административное производство», а также сложные связи между ними в сфере правовой доктрины. Правильное понимание и применение этих терминов имеет первостепенное значение для обеспечение эффективного правового регулирования и защиты прав, свобод и законных интересов физических и юридических лиц в их отношениях с органами государственного управления и судебной системой. Акцентировано на том, что использование специфических терминов в законодательных актах и правовых документов играет ключевую роль в формировании практики административного права. Несмотря на разницу в терминологии в разных странах с развитыми системами административного права, главная цель остается неизменной – достичь честного и справедливого административного процесса, поддерживающего права и интересы всех заинтересованных сторон. Проанализированы различия между административным процессом, административным процедурой и административным производством путем освещения их отдельного применения и последствий в юридической практике.
Administrative procedure and its relationship with related concepts
Keywords: адміністративний порядок; правова доктрина; адміністративне право; правове регулювання; права і свободи; адміністративна процедура; адміністративний процес; термінологія; administrative order; legal doctrine; administrative law; legal regulation; rights and freedoms; administrative procedure; administrative process; terminology; административный порядок; правовая доктрина; административное право; правовое регулирование; права и свободы; административная процедура; административный процесс; терминология